(untitled) (Dhaka University Law Journal, 2025)
This article focuses on the concepts of gift as a mode of transfer of property, including relevant case laws concerning the major thematic areas. Case laws dogma under this way of transfer of property will hold immense connotation in understanding legal concepts of disputed gift substances, where it is necessary to ensure fairness and justice. This article will also discern new interpretations of the laws of gift, both under the Transfer of Property Act 1882 and Muslim personal law. Dhaka University Law Journal, 2025, 36 (1), 1-25